Changes in Adolescents' COVID-19-Health-Related Stress, Parent-Adolescent Relationships, and Mental Health During the COVID-19 Pandemic: The Effect of Personality Traits. - Donker, Monika H.; Mastrotheodoros, Stefanos; Yanagida, Takuya; Branje, Susan (Journal of Youth & Adolescence, 2025)
Previous studies investigated short-term effects of COVID-19 on families. However, much is unknown about how families with adolescents fared throughout the pandemic, as well as factors that might explain interindividual differences in adjustment. The current study used latent change score models to investigate associations between changes in adolescents' mental health, parent-adolescent relationship quality, and COVID-19-health-related stress from Fall 2019 to Spring 2021, and whether personality predicted changes in adolescents' mental health, relationship quality, and stress. Participants were 242 adolescents (M = 11.56, SD = 0.44, 50% girls). Parent-adolescent negative interactions decreased from before the pandemic to the first lockdown, and stronger decreases (both in this period and between Fall 2020 and Spring 2021) were associated with simultaneous stronger increases in mental health. From Spring to Fall 2020, decreases in stress were stronger for less extraverted adolescents and were associated with better mental health. More agreeable adolescents reported a stronger decrease in stress between Fall 2020 and Spring 2021. The findings suggest that it is important to consider heterogeneity in designing future intervention and prevention programs. Especially adolescents with existing problems and from multi-problem families might be at risk for adverse consequences during pandemic-like situations.